KONSEP AL-MUJRIM DALAM QS. AL-KAHF [18]: 47-49 - Bahsoan, Agil (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2011)
Many people think that sin is merely doing what is prohibited and forbidden only. They forget that the first of iniquity to Allâh is leaving what was ordered, as when God commanded the devil prostrate to Adam, but Satan disobey His commands. This is the iniquity of Satan for the first time. Some scholars argue that all iniquity is a great sin. It looks like the scholars look of the Greatness of Allah Almighty and Exalted who disobeyed, so that even if the actual insubordination to his small, it still saw iniquity in him as a sin. In addition, many people do not know that in addition to the sin associated with the act limb zâhir as sin is born of the hands, feet, eyes, tongue, genitals and so there is also a sin that binds to the liver that cannot be seen by the eye but can be felt the impact, which is meant here is iniquity liver, such as cocky, riya, arrogant and so forth. These hearts are intrinsically more dangerous lawlessness of iniquity was born. Therefore this article will review the sin, the types of sins, causes the sinner based interpretation tahlîlî and mawdû?î in QS. al-Kahf (18) 47-49.